Accidental Online Political Engagement: The Role of Social Media Escapism in Online Political Participation - Hoffmann, Christian Pieter; Lutz, Christoph; Müller, Severina; Meckle, Miriam (AoIR Selected Papers of Internet Research, 2017)
Recently, much scholarship has investigated how social media affect citizens’ political participation, online and offline. In general, social media use has a positive but weak effect on participation. However, different use types exert a differentiated influence. While information-rich and active uses result in more participation, entertainment-oriented and passive uses lead to less participation. In this contribution, we introduce the concept of escapist Facebook use. We argue that Facebook might activate users to participate politically through what we call accidental political engagement, even if used in escapist ways. Based on a survey of 762 Facebook users in Germany and using linear regression, we test the influence of three Facebook use types on online political participation: consumptive, participatory and productive. Consumptive use has a negative and productive use a positive effect on online political participation. Escapism has a small positive effect. It moderates consumptive use negatively and productive use positively, strengthening existing tendencies.